From 'African Cinema' to film services industries: A cinematic fact. (1st March 2017) - Ureke, Oswelled; Tomaselli, Keyan
This article problematizes the universally used phrase 'African cinema' and explores how it can be examined in terms of a film services framework, which includes both industrial criteria and ideological shifts, as a way of deepening screen media studies in searching for a more holistic value chain framework. The main argument is that the idea of 'African cinema', especially as defined from racial, continental or ideological points of view, is outworn, reductive and in need of revision. The article complements other scholarly work situated in cinematic fact contexts of production.